Oral health status and treatment needs of military populations in Garoua, Cameroon - Ashu Michael Agbor; Karpal Singh; Clement Welyang; Tchweguem Clement; Etta Barnarbas Ebot; Anderson Tetmoun (Saudi Journal of Oral Sciences)
Introduction: Apart from training and combat injuries, dental emergencies can affect the efficiency of military personnel in the field. This is one of the reasons why the oral status of soldiers must be evaluated before deploying them. Aims: The objective of our study was to assess the oral health status of Cameroonian soldiers assigned to the third joint military region at Garoua. Methodology: We conducted a descriptive cross-sectional study between January 2022 and July 2022. Data on the sociodemographic profile, oral hygiene practices, dietary habits, and perceived oral care needs were collected using a questionnaire. Clinical examination was carried out to elucidate oral pathologies, and a logistical regression was performed to determine factors associated with oral disease with a P value set at < 0.05. Results: We recruited 288 military personnel aged 23 years, predominantly males; the mean duration of service with the military was 13.5 ± 12.5 s.d years and 182 (63.2%) had been to the war front. The majority 251 (87.2%) had visible plaque, 252 (87.5%) had calculus, and 6 (2.1%) had gum recession. The mean DMFT index was 0.80 and 4 (1.4%) had dental coronary fracture. The prevalence of dental caries was 44.4%, 87.2% had periodontal diseases with 85.77% gingivitis and 2.08% periodontitis. Two-thirds 193 (64.7%) of dental diseases were found among servicemen with secondary education. There was a statistically significant relationship between level of education and oral health status (*P = 0.05), between the oral condition and the consumption of sugary food (*P = 0.008), between oral condition and grade (*P = 0.03), between oral health practice and sugary food consumption (*P = 0.022), and between oral health and chewing gum consumption (*P = 0.029. Half (52.8%) needed dental restorations, 87.8% periodontal treatment, 246 (85.4%) scaling, and 6 (2.1%) deep scaling. Conclusion: The prevalence of dental caries and periodontal diseases was high, and three-quarters of servicemen were classified under grade 2 dental readiness.